Constructing roads - constructing risks?: settlement decisions in view of landslide risk and economic opportunities in Western Nepal - Lennartz, Thomas (Mountain research and development, 2013)
Government authorities and development agencies use road construction as a tool to support socioeconomic development in remote areas worldwide. In mountain regions, roads are closely connected with landslide risk. They destabilize slopes and often lead to the expansion of settlements into hazard zones. Weighing increased landslide risk against economic opportunities, inhabitants of adjacent areas acquire land along road corridors and build shops and houses. This article presents a case study from western Nepal, where an internationally supported road construction project triggered the establishment of a new bazaar in a landslide-prone area. Based on data gathered from qualitative interviews and a quantitative household survey, it discusses people's rationales for moving to the hazard zone, placing special emphasis on risk perception and economic reasoning from a livelihood perspective. The article also considers the extent to which the approach to rural road construction presently used in Nepal influences such developments. The study provides insights into the links between risk perceptions, livelihood strategies, and road-related development interventions and provides suggestions for a risk-sensitive adaptation of current approaches.
Accepted: September 2013
Gesehen am 20.01.2022